Electric Modulus Analysis of (1 − x) PbMg1/3Nb2/3O3-(x)K1/2Bi1/2TiO3 Ceramics - Kebede Legesse; Vijaya Bhaskar Rao Poluri; Elangovan Sampandam (Advances in Condensed Matter Physics)
Ferroelectrics refer to groups of dielectrics having the property of spontaneous polarization. Lead magnesium niobate-potassium bismuth titanate ((1 − x) PbMg1/3Nb2/3O3-(x)K1/2Bi1/2TiO3)) x = 0.15, 0.25, and 0.35 are prepared by solid-state reaction rout technique. The electric modulus of the prepared samples is studied using the complex impedance spectroscopic method at 400°C, 450°C, and 500°C in various frequency ranges. In the lower frequency range, the real modulus (M′ (ω)) decreased with increasing the temperature. Furthermore, the real modulus (M′ (ω)) increased with increasing frequency and the concentration of the doping component. The imaginary modulus (M″ (ω)) increased with increasing the temperature. The significant variations in the real and imaginary coefficients signify the existence of thermally activated dielectric relaxation between the selected components. Moreover, the magnitude of grain capacitance increased with increasing the temperature, confirming the negative temperature coefficient of resistance of the material.